Pengaruh Penerapan Studi Kasus terhadap Pengetahuan Pelanggaran Kode Etik Profesi Bidang IT bagi Mahasiswa Otomasi Sistem Permesinan - Nur Asmi Rahmawati (Indonesian Journal of Fundamental Sciences, 2018)
This study was conducted to determine the effect of the application of case studies on knowledge of violations of the professional code of ethics in the IT field for students majoring in Mechanical Systems Automation. The research method used was an experiment with the design of "one shot case study". The study was conducted on students who program Professional Ethics courses majoring in Mechanical Systems Automation.  The results of this study indicate that the value of students after doing a case study has increased. This shows that the case study method in this learning is appropriate to use.